Employability beliefs of business students by gender and year of study: Implications for higher education. Issue 2 (July 2022) - Bennett, Dawn; Ananthram, Subramaniam; Lindsay, Sophie; Benati, Kelly; Jevons, Colin
Abstract: Grounded in social-cognitive theory, the study reported here explored undergraduate business students' perceptions of their employability and the impact of year of study and gender on these perceptions. 6, 004 undergraduate business students enrolled with multiple Australian universities self-assessed their study and career-related confidence using an online, validated measure of perceived employability. Exploratory factor analysis was conducted and five predicted factors were obtained. Multivariate analysis of variance then identified gender and year-of-study differences across five employability factors. The findings highlight gender and year of study differences in students' understanding of how well their programs related to their future careers. The same differences were noted in students' confidence that their learning tasks were career-relevant and also their confidence that they could apply their learning in a workplace setting. Student confidence that their degree programs were preparing them for graduate life and work lessened as they progressed through their programs. Implications include the need for business educators to be clear about the relevance of each learning and assessment task, and to take a data-driven approach to informing career development learning activities in higher education. Highlights: The self-perceived employability of business students was explored using social-cognitive theory. Five employability constructs, gender, and year of study differences were empirically assessed. Both gender and study year impacted students' perceived program relevance and ability to find and maintain meaningful work. Student confidence declined through their degree program, with implications for student retention and satisfaction. Business educators should take a data-driven, whole-of-degree approach to informing career development learning activities.